Kriyakala: An Ayurvedic Perspective And Its Corelation With Biomarkers - Dr Amulya D; Dr Poornima P K M; Dr Bharath M S (Revista Electronica de Veterinaria, 2024)
The concept of Shat-Kriyakala (Stages of disease manifestation) emphasizes the significance of timely interventions in disease progression, strategically aligning therapeutic actions with the distinct stages of disease development. It guides the understanding of disease manifestation through the lens of doshic imbalances Vata (dosha regulating movement and cognition), Pitta (dosha regulating body temperature and metabolic activities), and Kapha (doṣha responsible for cohesiveness)—provoked by dietary, lifestyle, and environmental factors. Kriyakala encompasses into six stages, beginning with Sanchaya(Stage of a dosha increasing in its own location), where doshas accumulate in their natural sites, offering an opportunity for preventive strategies through lifestyle adjustments, Prakopa(Stage of a dosha reaching the threshold) and Prasara(Stage of a dosha spreading beyond its own location) avasta of Kriyakala representing a progressive state of imbalance and increasing specificity in symptoms along with complexity in management with poor prognosis. This concept parallels modern biomedicines use of biomarkers, which are biological indicators used to detect and measure diseases states or physiological changes. Biomarkers become vital for precise diagnosis and prognosis. Diagnostic biomarkers confirm the presence of illness, while prognostic biomarkers evaluate the potential for recurrence or progression. This framework not only facilitates early diagnosis and prevention but also enriches understanding of disease classification, especially in ailments like cancer and diabetes. The synergy of ancient wisdom with contemporary biomarker research promises enhanced health outcomes.